Benefits and Challenges of Over-Actuated Excitation Systems - Norman Fitz-Coy; Vivek Nagabhushan; Michael T. Hale (Shock and Vibration)
This paper provides a comprehensive discussion on the benefits and technical challenges of controlling over-determined and over-actuated excitation systems ranging from 1-DOF to 6-DOF. The primary challenges of over-actuated systems result from the physical constraints imposed when the number of exciters exceeds the number of mechanical degree-of-freedom. This issue is less critical for electro-dynamic exciters which tend to be more compliant than servo-hydraulic exciters. To facilitate the technical challenges discussion, generalized methods for determining the drive output commands and the actuator input transform is presented. To further provide insights into the problem, over-actuated 1-DOF and 6-DOF examples are provided. Results are presented to support the discussions.